Rancang Bangun Aplikasi Berkendara Sepeda Berbasis Virtual Reality dan Android dengan Menggunakan Metode Agile - Dwi Rahmadani, Inda; Ramadhan, M. Rizki; Istiqphara, Swadexi (ELECTRON Jurnal Ilmiah Teknik Elektro, 2022)
Body health is something that must always be maintained by everybody, because each activity carried out will be influenced by health conditions. In order for the body's health to always be in optimal condition, it is necessary to do several things including, adequate rest, consumption of healthy food and moving the body (exercise) which can be done by walking, running, exercising and cycling regularly. Cycling is a very good sport in moving the body and also gives users a different atmosphere because they can move from one area to another. However, some people do not have enough time and space to exercise bicycle outdoors. In this research, a cycling sports simulation software will be designed and built. This study aims to facilitate static bicycle users (static cycling) that can be used at home but can still enjoy the atmosphere when riding an outdoor bicycle, the atmosphere is created with virtual 3D consisting of buildings and parks on the side of the road that can be passed by virtual riders. This bicycle simulator software receives data from the microcontroller installed in the virtual bicycle to read the angular speed of the bicycle wheel which is then sent via Bluetooth communication and processed to move the virtual bicycle wheel to move around virtual roads. The method used in designing and implementing this software is the AGILE Software Development method. The obtained results indicate that the software can work well both in frame speed and system functionality